Aspects of mobile technology application in distance learning - V. V. Liakutin (Academy of Cognitive and Natural Sciences, 2015)
The purpose of this paper is to describe the use of mobile technologies in distance learning for further design and create a mobile software module for distance learning system (LMS) "Kherson Virtual University". Tasks assigned when creating mobile subsystem to simulate the learning process for the use of mobile applications. System design based on the model, a database of mobile application, mobile application class structure, the format of data transfer between client and server to implement a web service as an add-on server to access the mobile application to the API server. Implement a mobile-based application system Android. The object of study is a mobile application for educational purposes. The subject of the study is a mobile application that is running an operating system (OS) Android system for LMS "Kherson Virtual University". The paper presents the research methods: analysis of existing systems, analysis of didactic and technical requirements, modeling, design, development, mobile application architecture. The result of the study is to design the architecture of mobile applications, databases, and mobile application server, the structure of the server API, architecture classes of web service design data format.